Endoscopic submucosal dissection for premalignant lesions and noninvasive early gastrointestinal cancers - (:unkn) unknown (BAISHIDENG PUBLISHING GROUP INC, 2011)
AIM: To investigate the indication, feasibility, safety, and clinical utility of endoscopic submucosal dissection (ESD) in the management of various gastrointestinal pathologies. METHODS: The medical records of 60 consecutive patients (34 female, 26 male) who underwent ESD at the gastroenterology department of Kocaeli University from 2006-2010 were examined. Patients selected for ESD had premalignant lesions or non-invasive early cancers of the gastrointestinal tract and had erdoscopic and histological diagnoses. Early cancers were considered to be confined to the submucosa, with no lymph node involvement by means of computed tomography and endosonography. RESULTS: Sixty ESD procedures were performed. The indications were epithelial lesions (n = 39) (33/39 adenoma with high grade dysplasia, 6/39 adenoma with low grade dysplasia), neuroendocrine tumor (n = 7), cancer (n = 7) (5/7 early colorectal cancer, 2/7 early gastric cancer), granular cell tumor (n = 3), gastrointestinal stromal tumor (n = 2), and leiomyoma (n = 2). En bloc and piecemeal resection rates were 91.6% (55/60) and 8.3% (5/60), respectively. Complete and incomplete resection rates were 96.6% (58/60) and 3.3% (2/60), respectively. Complications were major bleeding [n = 3 (5%)] and perforations [n = 5 (8.3%)] (4 colon, 1 stomach). Two patients with colonic perforations and two patients with submucosal lymphatic and microvasculature invasion (1 gastric carcinoid tumor, 1 colonic adenocarcinoma) were referred to surgery. During a mean follow-up of 12 mo, 1 patient with adenoma with high grade dysplasia underwent a second ESD procedure to resect a local recurrence. CONCLUSION: ESD is a feasible and safe method for treatment of premalignant lesions and early malignant gastrointestinal epithelial and subepithelial lesions. Successful en bloc and complete resection of lesions yield high cure rates with low recurrence.
Keywords: Endoscopic submucosal dissection; Premalignant gastrointestinal lesion; Noninvasive early gastrointestinal cancer; Neuroendocrine tumor; Gastrointestinal stromal tumor; EARLY GASTRIC-CANCER; MUCOSAL RESECTION; UPDATE; TUMORS; TRACT; EMR